2020
DOI: 10.1186/s12957-020-01960-2
|View full text |Cite
|
Sign up to set email alerts
|

Colon metastasis from hepatocellular carcinoma: a case report and literature review

Abstract: Background: Hepatocellular carcinoma (HCC) is a malignant tumor with frequent intrahepatic metastases; extrahepatic metastases are not rare but less frequent compared to intrahepatic ones. The most frequent sites of extrahepatic metastases are the lungs, followed by the lymph nodes, bones, and adrenal glands. Case report covering gastrointestinal (GI) tract involvement from HCC is limited. Case presentation: A 60-year-old man was referred to us in May 2019 with a diagnosis of sigmoid colon tumor. The patient h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 23 publications
(18 reference statements)
0
10
0
Order By: Relevance
“… 7 A recent review by Yu et al regarding metastasis in patients with HCC surmised that upper GI sites (eg, stomach, duodenum) are more likely locations of metastasis because these are subject to direct invasion by the primary tumor. 8 Lower GI tract sites (eg, distal colon, rectum) otherwise are unlikely targets for metastasis because of their location far from direct invasion and downstream from portal venous flow. 8 The most frequent sites of colonic involvement include the ascending and transverse colon, with only one case reported of distal colonic involvement.…”
Section: Discussionmentioning
confidence: 99%
“… 7 A recent review by Yu et al regarding metastasis in patients with HCC surmised that upper GI sites (eg, stomach, duodenum) are more likely locations of metastasis because these are subject to direct invasion by the primary tumor. 8 Lower GI tract sites (eg, distal colon, rectum) otherwise are unlikely targets for metastasis because of their location far from direct invasion and downstream from portal venous flow. 8 The most frequent sites of colonic involvement include the ascending and transverse colon, with only one case reported of distal colonic involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that hepatocellular carcinoma and colorectal cancer are among the most common and fatal cancer types 2 , 3 . Hepatocellular carcinoma (HCC) is a worldwide health care issue that accounts for a high rate of mortality 2 , 4 . Many factors are associated with HCC development, including chronic infections with hepatitis viruses (hepatitis B and C), aflatoxin exposure, obesity, prolonged and/or heavy alcohol consumption 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The aggressiveness of HCC is associated with a high mortality rate due to early recurrence and its distant metastasis to the lungs, brain, lymph nodes, adrenal gland, bones, and the peritoneum and/or omentum [2]. Recent case reports have implicated HCC in extrahepatic metastasis of the colon [3], spine [4], cervical [5], and kidney [6]. The most common approach to the treatment and management of HCC include hepatectomy and hepatic transplantation [7].…”
Section: Introductionmentioning
confidence: 99%